Profil HPV Genotyping dan Pap Smear LBC di MRCCC Siloam Hospitals Semanggi - Calista, Angeline; Sugiharto, Sony (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Cervical cancer is the second most common malignancy among Indonesian women after breast cancer, with 36,964 cases and 20,708 deaths in 2022. Cervical cancer screening studies using HPV genotyping and pap smear LBC have already been conducted in Indonesia using different methods. Purpose: The objectives of this study were to determine the HPV prevalence and genotype distribution, also the cytological results at MRCCC Siloam Hospitals Semanggi. Methods: A descriptive study with a cross-sectional design was conducted using 599 samples selected by consecutive non-random sampling from 2023–2024. HPV genotyping was performed using the DiagCor GenoFlow™ HPV array test, and pap smear analysis was conducted using PathTezt™ liquid-based cytology. Results: This study found 18.2% patients positive for HPV, comprising 58.7% with high-risk HPV only, 23% with low-risk HPV only, and 18.3% with mixed HPV infection Among all HPV-positive women, 53.2% had multiple HPV infections. The prevalence of high-risk HPV infection was 62.4%, with the most frequently detected genotypes were HPV-68, HPV-66, and HPV-52. The most frequent low-risk HPV infections were HPV-42, HPV-43, and HPV-44. Abnormal cytology results were found in 2.8% of patients, specifically ASC-US, LSIL, ASC-H, and AGC. Conclusion: The most prevalent HPV genotypes identified were HPV-68 (10.1%) and HPV-66 (9.6%). The study concludes that a positive HPV test is not always accompanied by abnormal cytology results. Therefore, HPV genotyping should be performed in conjunction with cytological examination for comprehensive screening.